(Ng@NTER MUZYKA TRETXEGO TE^ENIQ {ULLERs (Nu^EBNOE POSOBIEs - (NpOLI]UK(B. (Na(B.(N|(B.s ((NsANKT (B-(NpETERBURGs (NlANXs, 2021)
(Nu^EBNOE POSOBIE POSWQ]ENO g@NTERU {ULLERU (B-(NAMERIKANSKOMU KOMPOZITORU(B, (NISPOLNITEL@(B, (NMUZYKOWEDU(B, (NDIRIVERU(B, (NPEDAGOGU(B. (NAWTORU TERMINA(B.s
Keywords: (NmETODIKAs